ALLELOPATHIC EFFECTS OF ARABICA COFFEE (Coffea arabica) ON GERMINATION AND GROWTH OF UPLAND RICE VARIETY MAPAN P-02 (Oryza sativa) - Sipahutar, Lasro Yulistiawati; Nugroho, Wahyu; Susilawati, Puspita Ratna (Universitas Tanjungpura, 2025)
Coffea arabica is generally a monoculture, resulting in a lack of land for other crops, especially staple foods such as rice. One way to optimise land utilisation is through intercropping. This study aimed to determine the effect of Coffea arabica allelopathy on germination and growth of upland rice variety Mapan P-02 (Oryza sativa). The method used in this study was a completely randomised design (CRD) with the treatment of variations in the concentration of Coffea arabica allelopathy, namely 2.5; 5; 7.5; and 10% with five repetitions. The data obtained were analysed using One-Way ANOVA. The results showed that the effects of Coffea arabica allelopathy with different concentrations did not significantly differ on plant height, number of leaves, wet weight, and dry weight of upland rice of established variety Mapan P-02 (Oryza sativa). This research implies that upland rice of the established variety Mapan P-02 can be used as a companion plant for Coffea arabica in the intercropping system.